Apparent diffusion coefficient values and non-homogeneity of diffusion in brain tumors in diffusion-weighted MRI. (February 2020) - Basirjafari, Sedigheh; Poureisa, Masoud; Shahhoseini, Babak; Zarei, Mohammad; Aghayari Sheikh Neshin, Saeideh; Anvari Aria, Sheida; Nouri-Vaskeh, Masoud
Background: The values that have been received from apparent diffusion coefficient (ADC) maps of diffusion-weighted magnetic resonance imaging (DW-MRI) might play a vital role in evaluating tumors and their grading scale. Purpose: To investigate the predictive role of this heterogeneity in brain tumor pathologies and its correlation with Ki-67. Material and Methods: A total of 124 patients with brain tumors underwent brain MRI with gadolinium injection. ADC and standard deviation of each lesion have been obtained from manual localization of the region of interest on the ADC map. A receiver operating characteristic analysis was conducted to determine the minimum cut-off values of the mean ADC and mean standard deviation of ADC maps having the highest sensitivity and specificity to differentiate high-grade and low-grade tumors. Results: Mean ADC values in the region of interest were significantly lower for malignant tumors (grade IV and metastasis) than grade I brain tumors, while a higher mean standard deviation was observed. In a more detailed comparison of tumor groups, the mean standard deviation of the ADC for glioblastoma multiform was significantly higher than meningioma grade I ( P  < 0.001) and metastasis was significantly higher than grade III and IV astrocytic tumors ( P  = 0.004). The analysis of Ki-67 proliferation index and mean ADC values in gliomas showed a significant inverse correlation between the parameters (r = –0.0429, P  < 0.001) and direct correlation between Ki-67 and mean standard deviation of the ADC (r = 0.551, P  < 0.001). As an index for the ADC to differentiate high-grade and low-grade tumors, the cut-off values of 1.40*10 −3  mm 2 /s for mean ADC and 45*10 −3  mm 2 /s for mean standard deviation have the highest combination of sensitivity, specificity, and area under the curve. Conclusion: The mean value and standard deviation of the ADC could be considered for differentiating between low-grade and high-grade brain tumors, as two available non-invasive methods.